2015
DOI: 10.1080/13548506.2015.1051556
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in alcohol prototype perceptions and willingness to drink in UK adolescents

Abstract: Using the Prototype Willingness Model (PWM) as a framework, this study sought to explore the relationship between prototype perceptions, willingness and alcohol consumption in a sample of adolescents in the United Kingdom. Adolescents aged 11-17 were asked about their alcohol prototype perceptions, willingness to drink, intentions, alcohol consumption, drunkenness and harms using a cross sectional online survey. Participants were recruited through opportunity sampling via schools and parents. The survey was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…Recent longitudinal research supports the theoretical assumptions within the PWM as applied to adolescents in the United States, where prototype favourability predicted willingness six months later, which predicted subsequent drinking behaviour after a further six months (Litt & Lewis, 2016). Research in the UK has also supported this relationship and found that drinker prototypes are more positive in older adolescents than in younger adolescents (Davies et al, 2016).…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations
“…Recent longitudinal research supports the theoretical assumptions within the PWM as applied to adolescents in the United States, where prototype favourability predicted willingness six months later, which predicted subsequent drinking behaviour after a further six months (Litt & Lewis, 2016). Research in the UK has also supported this relationship and found that drinker prototypes are more positive in older adolescents than in younger adolescents (Davies et al, 2016).…”
Section: Introductionmentioning
confidence: 61%
“…There is a growing body of evidence to support the use of this theory in understanding risky drinking in young people (Davies et al, 2016;Litt et al, 2014;Zimmermann & Sieverding, 2011). Recent longitudinal research supports the theoretical assumptions within the PWM as applied to adolescents in the United States, where prototype favourability predicted willingness six months later, which predicted subsequent drinking behaviour after a further six months (Litt & Lewis, 2016).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…The consequences of excessive drinking assessed within AUDIT include memory loss and guilt/ remorse but this tool does not assess more specific short-term impacts that are often experienced by students (Davies & Joshi, 2018). Drinking-related harms experienced in the last four weeks were therefore measured using a scale used in a previous study with UK students (Davies, Martin, & Foxcroft, 2016) and included: being sick; embarrassed; missing class; trouble with police; injury; taken to hospital; having a fight; taking an illegal drug; losing a personal item such as a phone; unprotected sex; regretted sex; not knowing where you are when you woke up; an embarrassing photo posted on social media (14 items; T1 α=.751; T2 α=.725). These items focus on short-term consequences of alcohol consumption, rather than problematic use and dependence as measured by items 4-10 of the AUDIT scale.…”
Section: Alcoholmentioning
confidence: 99%